2004
DOI: 10.1068/p5162
|View full text |Cite
|
Sign up to set email alerts
|

Does Previewing One Stimulus Feature Help Conjunction Search?

Abstract: We examined the effects of previewing one aspect of a search display, in order to determine what subset of display information is most useful as a prelude to a search task. Observers were asked to indicate the presence or absence of a known target, in a conjunction search where the target was defined by the combination of colour and orientation (a yellow horizontal line presented among yellow vertical and pink horizontal distractors). In the colour preview condition of experiment 1, observers were first shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
4
13
1
Order By: Relevance
“…Reali, Spivey, Tyler, and Terranova (2006) provided further confirmation by replicating the findings of Spivey et al (2001), while also showing that the order in which information is delivered matters: Describing the target using color followed by orientation facilitated search more than did the opposite order. This echoes findings by Olds and Fockler (2004), who found a similar order effect using visual preview of stimuli. Crucially, Reali et al (2006)'s design excludes the possibility that linguistic guidance effects are an artefact of blocked designs, or that they are due to an odd-one-out search strategy.…”
Section: Visual Searchsupporting
confidence: 89%
See 2 more Smart Citations
“…Reali, Spivey, Tyler, and Terranova (2006) provided further confirmation by replicating the findings of Spivey et al (2001), while also showing that the order in which information is delivered matters: Describing the target using color followed by orientation facilitated search more than did the opposite order. This echoes findings by Olds and Fockler (2004), who found a similar order effect using visual preview of stimuli. Crucially, Reali et al (2006)'s design excludes the possibility that linguistic guidance effects are an artefact of blocked designs, or that they are due to an odd-one-out search strategy.…”
Section: Visual Searchsupporting
confidence: 89%
“…Faster versus slower search is known to be affected by a variety of factors, including, among others, the extent to which a display affords the formation of perceptual groups (He & Nakayama, 1995;Nakayama & Joseph, 1998;Nakayama & Silverman, 1986;Nordfang & Wolfe, 2014); the salience of individual features that are reliably correlated with a conjunction (Found, 1998;Sobel & Cave, 2002;Wolfe, Cave, & Franzel, 1989); and the similarity between target and distractors, as well as the specificity of the template (Duncan & Humphreys, 1989;Malcolm & Henderson, 2009). Guidance (Olds, Cowan, & Jolicoeur, 2000a,b,c) or preview of features in a target conjunction (Olds & Fockler, 2004) also facilitates search for complex targets. Palmer, 1994Palmer, , 1995Vickery, King, & Jiang, 2005); and by the search strategy afforded by the display (e.g., the presence of subsets; cf.…”
Section: Visual Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…This asymmetry is consistent with the preferred order of feature type delivery observed in other studies. For example, Olds and Fockler (2004) conducted purely visual experiments with no linguistic input in which they found greater search assistance from single-feature previews that primed color first and then orientation than from those that primed orientation first and then color, suggesting that the cause of the asymmetry may reside in visual discrimination or localization of color versus visual discrimination or localization of orientation. Moreover, Boucart and Humphreys (1997) reported that in a matching task attention could be efficiently applied to color without influence from semantic information regarding the objects, but semantic information did interfere with attention to orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Examining practices such as priming through previewing various aspects of objects would also be interesting. For example, Olds and Fockler [2004] compare the previewing of color and orientation, and show that conjunction previewing is most effective. Furthermore, Watson et al [2003] demonstrated that, with previewing, more delay can be tolerated even when the task is difficult.…”
Section: Future Workmentioning
confidence: 99%